P.S. I like you - West, Kasie (2016)
Every day in chemistry class, high school student and aspiring songwriter Lily Abbott is finding notes left to her by a mystery boy, love letters really, and she hopes they are from Lucas, a boy she is attracted to--so when she finds out they are really from, she is shocked and unsure about how to respond
Keywords: Sexual attraction -- Juvenile fiction; Emotions in adolescence -- Juvenile fiction; Dating (Social customs) -- Juvenile fiction; Composition (Music) -- Juvenile fiction; High schools -- Juvenile fiction; Fiction; Juvenile works